Analisis Berpikir Tingkat Tinggi Menyelesaikan Soal Cerita Matematika Siswa Kelas VII Semester Genap Di SMP Negeri 1 Colomadu Tahun 2015/2016 - Maulana, Imron; , Prof. Dr. Sutama, M.Pd (2016)
The purpose of research is to describe the high-level thinking skills in aspects of analyzing, evaluating, creating in solving mathematical word problems. This type of research is based on qualitative ethnographic design. When the study in the second semester of the 2015/2016 academic year. The research subject teachers and students of SMP Negeri 1 Colomadu. Test data collection techniques, interviews, and documentation. The validity of the data using a triangulation of sources and techniques. Data were analyzed using method three grooves. The study states the ability to think critically aspect analyze the observed achievement indicators (1) the student is able to distinguish the problem into its elements have not been fulfilled due to the habit is given about the short application (2) the student is able to organize the elements in order to achieve coherence yet to be met on the basis of capacity transform into a mathematical model and still not up (3) students were able to attribute the problems have not been fulfilled due to not accustomed to communicating ideas and concepts. The ability to think critically evaluate aspects observed indicators of achievement (1) to re-examine the job properly, have not been fulfilled due to students not accustomed to answer in a systematic and structured (2) critiquing the problems, has not been met because of the mastery of basic concepts is not maximized. The ability to think critically aspects of creating observed on the achievement of indicators (1) the student is able to formulate a settlement / different solutions have not been met because students rarely given the problems of open (2) the student is able to plan the right solution in accordance with the problems, has not been met due to students' difficulties in planning settlement (3) the students are able to produce the elements there to be a single entity have not been fulfilled due to the mastery of the basic concepts of calculation has not fully mastered.